Blurred lines. Eosinophilic COPD: ACOS or COPD phenotype? - Loureiro, Cláudia Chaves (2016)
Because asthma and COPD are both inflammatory chronic obstructive airway diseases, there are several clinical expressions which can cause confusion, such as: eosinophilic asthma with fixed obstruction, which is a risk factor and might progress to COPD; eosinophilic COPD; COPD with partial reversible obstruction with no asthmatic component and also eosinophilic asthma-COPD overlap syndrome (ACOS). While at the two extremes of these disorders the pathoimmunological processes are clearly different, in some patients there is overlap and the pathophysiological border between asthma and COPD is fused (or diffuse). The current guidelines are clearly insufficient for classification of the obstructive patients and, taking into account that binary separation between the two diseases is not completely clear, we should resist the temptation to label patients as ACOS and consider new airway disease taxonomy. Regardless of the condition concerned, eosinophils should be considered in the algorithm approach to obstructive patients: in COPD, as in asthma, they are related to the underlying pathological process; they have prognostic value and are related to therapeutic response. Therefore, eosinophils should be valued as useful biomarkers and included in a multidimensional diagnostic and therapeutic approach, bearing in mind the phenotypic, immunopathological and functional complexity of chronic obstructive airway disease.